Städtebaulicher Investitions- und Förderbedarf 2020-2030. - Spars, Guido; Heinze, Michael; Gornig, Martin; Blazejczak, Jürgen; Untiedt, Gerhard; Alecke, Björn (My University, 2021)
Die Kommunen stehen großen Herausforderungen gegenüber: der demografische Wandel und neue Lebensbedingungen verändern die Nachfrage nach technischer und sozialer Infrastruktur. Es gilt, lebendige und identitätsstiftende Stadt-und Ortskerne zu erhalten bzw. zu schaffen, die Städte und Gemeinden an den Klimawandel anzupassen sowie bedarfsgerechten Wohnraum zu bauen. Die Städtebauförderung kann diesen Herausforderungen begegnen, in dem sie Investitionen in die städtische Infrastruktur, den Gebäudebestand sowie Grün-und Freiflächen ermöglicht. Vor diesem Hintergrund war es das Ziel des Forschungsprojektes, den zukünftigen Investitions-und Förderbedarf für den Zeitraum von 2020–2030 zu ermitteln. Darüber hinaus soll analysiert werden, inwieweit sich die Bedeutung einzelner Handlungsfelder der Städtebauförderung in Zukunft verändert und ob sich daraus Konsequenzen für den Investitions-und Förderbedarf ergeben. Das Forschungsprojekt basiert im Wesentlichen auf einem methodischen Dreiklang, der sich wechselseitig ergänzt und prüft: Erstens, einer Befragung der Bundesländer zum zukünftigen Investitions-und Förderbedarf, zweitens einer Befragung der Kommunen zum zukünftigen Investitionsbedarf sowie einer volkswirtschaftlichen Plausibilisierung der gewonnenen kommunalen Befragungsergebnisse.

For several decades, urban development funding has proven to be an efficient funding instrument with the aim of developing cities and communities in Germany in a sustainable and future-oriented manner. The federal government alone has invested approx. €790 million each year since 2017 in urban development funding. In addition, the federal government has made funding of €200 million available every year from 2017 to 2020 as part of the “Social Integration in the Neighbourhood” investment pact for the renewal, building and development of social infrastructure. At the same time, local authorities are facing serious challenges: demographic changes and new living conditions are changing the demand for technical and social infrastructure. Lively and identity-shaping city and town and centres have to be maintained or created, cities and communities have to be adapted to climate change and needs-based housing has to be built. Urban development funding can rise to these challenges by enabling investments in urban infrastructure, in existing buildings, as well as in green and open spaces. Against this background, the aim of this research project was to determine the future investment and financing requirements for the period from 2020 to 2030. A further aim has been to analyse the extent to which the significance of specific action areas of urban development funding will change in future and whether this will lead to consequences for investment and financing requirements.
Keywords: Städtebauförderung; Förderungsprogramm; Investitionsbedarf; Bedarfsentwicklung; Gemeinde; Bundesland; Befragung; Bedarfsprognose